2017
DOI: 10.1016/j.bbalip.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

New insight into the interaction of TRAF2 C-terminal domain with lipid raft microdomains

Abstract: In this study we provide the first evidence of the interaction of a truncated-TRAF2 with lipid rafts microdomains. We have analized this interaction by measuring the diffusion coefficient of the protein in large and giant unilamellar vesicles (LUVs and GUVs, respectively) obtained both from synthetic lipid mixtures and from natural extracts. Steady-state fluorescence measurements performed with synthetic vesicles indicate that this truncated form of TRAF2 displays a tighter binding to raft-like LUVs with respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…demonstrate that the protein modifies the order of the phospholipids in the lipid bilayer in opposite ways, and to a different extent, depending on the temperature. In a recent study , we have reported the effects that TRAF2 exerts on giant unilamellar vesicles, as observed by confocal fluorescence microscopy. In particular, it was shown that the protein induces the formation of intraluminal vesicles, especially in the presence of the ganglioside GM1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…demonstrate that the protein modifies the order of the phospholipids in the lipid bilayer in opposite ways, and to a different extent, depending on the temperature. In a recent study , we have reported the effects that TRAF2 exerts on giant unilamellar vesicles, as observed by confocal fluorescence microscopy. In particular, it was shown that the protein induces the formation of intraluminal vesicles, especially in the presence of the ganglioside GM1.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular dynamics simulations have suggested that the most flexible region of the truncated TRAF2 monomers is the N‐terminal domain, which is probably characterized by a loosening of the α‐helix that, in the full‐length TRAF2 oligomer, participates in the coiled coil motif . It was therefore proposed that the mechanical strength exerted by TRAF2 on the membrane occurs through the interaction of this region with ganglioside GM1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, TRAF2 dimers form hetero-trimeric oligomers with TRAF1 (i.e., TRAF1: [TRAF2] 2 ), which displays an enhanced propensity in cIAPs binding [ 22 ]. Finally, the protein C-terminal domain, TRAF2-C, strongly interacts with membranes when dissociated into monomeric/dimeric forms [ 27 , 28 ]. All these findings suggest that the oligomerization process might have a regulatory function on the TNF signaling in vivo.…”
Section: Introductionmentioning
confidence: 99%